INVESTIGATING STUDENTS’ VOCABULARY MASTERY TAUGHT USING VIDEO AND PICTURE AT SECONDARY SCHOOL: AN EXPERIMENTAL STUDY - Shandy Rahayu Ramadhan Putri; Nasrullah Nasrullah; Emma Rosana Febriyanti (INOVISH JOURNAL, 2023)
The purpose of this study is to determine whether there is a difference in students' vocabulary mastery when taught using video and picture. The researcher in this study utilized a variety of videos instead of just focusing on one type, which differentiates it from the previous study. The goal of this study is to compare the studentsâ€™ learning outcomes who were taught using video and using picture. SMP Negeri 14 Banjarbaru is where this study was conducted. In this study, a quantitative approach and a quasi-experimental design were applied. VIII C was designated as the experimental group, whereas VIII D was designated as the control group. The results of this study revealed that the experimental class's pre-test mean score was 71,1 and their post-test score was 82,6. Meanwhile, the pre-test mean score for students in the control group was 65,1 and the mean post-test score was 65,7. The researcher calculated the data using SPSS 26.0 and discovered that the Mann- Whitney U Test had an Asymptotic.Significance (2-tailed) is 0.04, indicating that it was lesser than 0.05. Therefore, it can be stated that there is a difference between students' vocabulary mastery taught using video and using picture, and the null hypothesis (H0) is rejected. As a result, it is possible to assume that the use of video as a teaching and learning media at SMP Negeri 14 Banjarbaru gave more effect in terms of students' vocabulary mastery than picture. The researcher advises English teachers to utilize videos into their lesson plans and to combine two or three different types of media to make their lessons more engaging and enjoyable for the students. As for future researchers, the researcher suggested conducting research in the same topic using more advanced and modern audio-visual media and visual media.Â